2003
DOI: 10.1038/sj.npp.1300244
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Benzamide Antipsychotic Amisulpride get into the Brain?—An In Vitro Approach Comparing Amisulpride with Clozapine

Abstract: This study evaluated the disposition of the two atypical antipsychotics, amisulpride (AMS) and clozapine (CLZ), and its main metabolite N-desmethylclozapine (DCLZ), to their target structures in the central nervous system by applying an in vitro blood-brain barrier and blood-cerebrospinal fluid (CSF) barrier based on monolayers of porcine brain microvessel endothelial cells (PMEC) or porcine choroid plexus epithelial cells (PCEC). Permeation studies through PMEC-and PCEC-monolayers were conducted for 60 min at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
(37 reference statements)
2
26
0
Order By: Relevance
“…24 Both studies concluded that ABCB1 genotyping should be considered to achieve optimal clozapine therapy. Several in vitro [28][29][30][31][32] and in vivo 20,33,34 studies reported that clozapine is not a substrate or a poor substrate of P-gp. 32 In contrast, clozapine metabolite N-desmethylclozapine has been shown to be a strong substrate to P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…24 Both studies concluded that ABCB1 genotyping should be considered to achieve optimal clozapine therapy. Several in vitro [28][29][30][31][32] and in vivo 20,33,34 studies reported that clozapine is not a substrate or a poor substrate of P-gp. 32 In contrast, clozapine metabolite N-desmethylclozapine has been shown to be a strong substrate to P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…This long-lasting effect is probably due to the limited ability for amisulpiride to cross the blood-brain barrier and its negligible metabolism. Amisulpiride is one of the most hydrophilic antipsychotics and has difficulty permeating the blood-brain barrier (Hartter et al 2003), entering the CNS via a slower and less efficient mechanism through the choroid plexus. Its elimination from the body is mainly accomplished by renal clearance, which is a slow process because it is substantially reabsorbed from the distal portion of the nephron.…”
Section: Discussionmentioning
confidence: 99%
“…For amisulpiride, on day 6 postpartum, the first maternal behavior test commenced 0.5 h before drug injections, and the remaining tests were done at 3.5, 4.0, 5.0, and 7.0 h after the drug injections. The first drug test was at 3.5 h postinjection instead of the more standard 0.5 h postinjection because amisulpiride enters the brain via the choroid plexus, and this mechanism of entry is slower than other drugs (Hartter et al 2003). As mentioned above, our in vivo occupancy studies in rats show that even at 6 h postinjection, amisulpiride at 10, 30, and 100 mg/kg still gives rise to 60, 81, and 87% D 2 occupancies, respectively, a level of occupancies comparable to that observed in antipsychotictreated patients.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining seven drugs were false negatives since they were not BDDCS class 1. Saturable uptake processes have been implicated in the transport of amisulpride [125] and gabapentin [126,127] into the brain. Four other false negatives have been reported to be substrates for uptake transporters expressed in the brain [128]: rosuvastatin (OAT3, OATP1A2, OATP1B1, and OATP2B1) [129131], zidovudine (OAT1, OAT2, OAT3, and OAT4) [132], trimethoprim (OCT2) [133], and chloroquine (OCT2) [133].…”
Section: Elaboration Analysis and Application Of Rules For Brainmentioning
confidence: 99%